Disclosure of Corporate Social Responsibility, Company Performance, and Corporate Reputation as the Mediating Role: Indonesian Context - Wuryan Andayani (Universitas Muhammadiyah Yogyakarta, Indonesia, 2021)
Research aims: This study aims to provide new empirical evidence regarding CSR practices and their impacts on firm performance and corporate reputation in the context of a developing country region, namely Indonesia.Design/Methodology/Approach This research samples were 70 companies listed on the Indonesia Stock Exchange with five years of observation. This study used secondary data, which already exists and was obtained from the Indonesia Stock Exchange's official website. Also, Partial Least Square was employed to test the hypothesis's parameter estimates.Research findings: The results revealed that CSR disclosure could improve firm performance but could not increase corporate reputation. Thus, companies that carry out CSR activities and pay attention to stakeholders mean that they (employees, customers, suppliers, investors, etc.) will contribute to the company’s economic performance. The results of this study also uncovered that the level of investor awareness of corporate reputation was still low. Investors were only oriented to short-term investments and did not care about the long-term viability of the company. It showed that corporate reputation did not fully mediate the relationship between CSR disclosure and company performance.Theoretical contribution/Originality: As this study develops scientific research in the fields of CSR, corporate performance, and corporate reputation as the mediating role, the findings of this research support the stakeholder theory that a company not only increases profits but also should be accountable to all stakeholders. Besides, corporate reputation partially mediated the relationship between CSR and firm performance. It indicated that in Indonesia, concern for corporate reputation was still low.